2009
DOI: 10.1111/j.1476-5381.2009.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

IGF‐1 derived small neuropeptides and analogues: a novel strategy for the development of pharmaceuticals for neurological conditions

Abstract: Insulin-like growth factor-1 (IGF-1) is neuroprotective and improves long-term function after brain injury. However, its clinical application to neurological disorders is limited by its large molecular size, poor central uptake and mitogenic potential. Glycine-proline-glutamate (GPE) is naturally cleaved from the IGF-1 N-terminal and it is also neuroprotective after ischemic injury, which provided a novel strategy of drug discovery for neurological disorders. GPE is not enzymatically stable, thus intravenous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 78 publications
0
53
0
1
Order By: Relevance
“…In a more recent study it was suggested that smaller peptide fragments, derived from IGF-1, could have advantages over growth factors in the treatment of brain injury. These fragments could be modified and designed with suitable properties to overcome many of the limitations associated with the native endogenous peptides regarding their potential role as medical drugs [68].…”
Section: Gh and Neuroprotectionmentioning
confidence: 99%
“…In a more recent study it was suggested that smaller peptide fragments, derived from IGF-1, could have advantages over growth factors in the treatment of brain injury. These fragments could be modified and designed with suitable properties to overcome many of the limitations associated with the native endogenous peptides regarding their potential role as medical drugs [68].…”
Section: Gh and Neuroprotectionmentioning
confidence: 99%
“…While the neuroprotective effect of IGF-1 is clearly mediated by IGF-1 receptors [16], the mode of action of GPE and cGP remains unclear as GPE does not bind to the IGF-1 receptor [32,34,68,73]. Despite the failure to identify a specific receptor, the neuroprotective effects of GPE and cGP after central (ICV) administration are clearly dose-dependent, consistent with receptor-mediated pharmacodynamics [73].…”
Section: Vascular Protection Of Cgp Was Mediated Via Activation Of Igmentioning
confidence: 87%
“…Inhibition of injuryinduced inflammation responses has also been suggested by the association of neuroprotection with these derivatives, and subsequently reduced levels of pro-inflammatory cytokines (IL-6 and TNF-a) and numbers of reactive microglia [60][61][62][63]. Furthermore, there was evidence of improved vascular remodeling, probably through either elevation in and/or protection of activation of astrocytes [73].…”
Section: Mechanisms Of Neuroprotection 41 Anti-apoptosis and Anti-inmentioning
confidence: 94%
See 2 more Smart Citations